ประสิทธิผลการป้องกันและปราบปรามอาชญากรรมของกองบังคับการตำรวจภูธรจังหวัดชลบุรี กองบัญชาการตำรวจภูธรภาค 2 สำนักงานตำรวจแห่งชาติ - อิทธิยาภรณ์, เฉลิมพรหม; หวังมหาพร, ปิยากร (Journal of Research and Curriculum Development, 2016)
การวิจัยครั้งนี้มีวัตถุประสงค์เพื่อ (1) ศึกษาระดับประสิทธิผลการป้องและปราบปรามอาชญากรรมของกองบังคับการตำรวจภูธรจังหวัดชลบุรี (2) ศึกษาปัจจัยที่ส่งผลต่อประสิทธิผลการป้องกันและปราบปรามอาชญากรรมของกองบังคับการตำรวจภูธรจังหวัดชลบุรี (3) ศึกษาปัญหาและอุปสรรคที่เกิดขึ้นในการดำเนินงานด้านการป้องกันและปราบปรามอาชญากรรมของกองบังคับการตำรวจภูธรจังหวัดชลบุรี และ (4) ศึกษาแนวทางการแก้ไขปัญหา และยกระดับประสิทธิผลการดำเนินงานด้านการป้องกันและปราบปรามอาชญากรรมของกองบังคับการตำรวจภูธรจังหวัดชลบุรี การวิจัยใช้ระเบียบวิธีวิจัยแบบผสมผสาน กลุ่มตัวอย่าง คือ เจ้าหน้าที่ตำรวจของกองบังคับการตำรวจภูธรจังหวัดชลบุรี จำนวน 357 คน จาก 23 โรงพัก และประชาชนผู้ใช้บริการจากสถานีตำรวจ 12 โรงพัก จำนวน 12 คน เก็บข้อมูลด้วยแบบสอบถาม การสัมภาษณ์แบบเจาะลึก และการสนทนากลุ่มย่อย ผลการศึกษา ปัจจัยที่ส่งผลต่อประสิทธิผลการป้องกันและปราบปรามอาชญากรรม พบว่า ปัจจัยด้านภาวะผู้นำตำรวจยุคใหม่มีค่าเฉลี่ยสูงที่สุด รองลงมาคือ วัฒนธรรมองค์กร ทีมข้ามสายงานการกำหนดกลยุทธ์ การประเมินผล และทรัพยากรการบริหาร ตามลำดับ สำหรับประสิทธิผลของการป้องกันและปราบปรามอาชญากรรมของกองบังคับการตำรวจภูธรจังหวัดชลบุรีในภาพรวมมีค่าเฉลี่ยอยู่ในระดับมาก โดยด้านการให้บริการของสถานีตำรวจมีค่าเฉลี่ยสูงที่สุด รองลงมาคือ ด้านการพัฒนางานตำรวจ ด้านการยกระดับความสามารถในการปฏิบัติ ด้านการสร้างความเข้มแข็งในการบริหารงาน และด้านการมีส่วนร่วมของประชาชนและเครือข่าย ตามลำดับ สมการพยากรณ์ที่ได้จากการวิเคราะห์แบบถดถอยพหุคูณเพื่อทดสอบสมการทำนายระดับประสิทธิภาพการป้องกันและปราบปรามอาชญากรรมของกองบังคับการตำรวจภูธรจังหวัดชลบุรีกับปัจจัยที่ส่งผลต่อประสิทธิผลการป้องกันและปราบปรามอาชญากรรม พบว่า มีความสัมพันธ์กันในทางบก (0.427) อย่างมีนัยสำคัญทางสถิติที่ระดับ 0.01 และเมื่อวิเคราะห์ถดถอยพหุคูณเพื่อทดสอบสมการทำนาย พบว่า ภาวะผู้นำตำรวจยุคใหม่ (MPL) การวางแผนกลยุทธ์ (SM) และทีมข้ามสายงาน (CFT) สามารถพยากรณ์ประสิทธิผลการป้องกันและปราบปรามอาชญากรรม (CE) ได้ร้อยละ 37 (R2 = 0.375) เขียนสมการพยากรณ์ในรูปแบบคะแนนดิบได้ดังนี้ CE = 2.912 + 0.260 (MPL) + 0.104 (SM) + 7.205 (CFT) แสดงให้เห็นว่า ภาวะผู้นำตำรวจยุคใหม่เป็นปัจจัยที่ส่งผลต่อประสิทธิผลการป้องกันและปราบปรามอาชญากรรมในลำดับแรก The Effectiveness of Crime Prevention and Suppression of Chonburi Provincial Police Division, Provincial Police Bureau Region 2, Royal Thai Police The objectives of this research were: (1) to study the level of effectiveness ofcrime prevention and suppression, (2) to study the factors that affect the effectiveness ofcrime prevention and suppression, (3) to study the problems and obstacles that occur inthe operation of crime prevention and suppression, and (4) to study the appropriateapproaches to solving problems and enhancing the level of effectiveness of crimeprevention and suppression of the Chonburi provincial police division. This studyemployed a mixed methodology. The sample of 357 police officers from 23 policestations in the Chonburi provincial police division and the sample of 12 people receivingservice from 12 police stations were obtained in this study. The data were collectedthrough the use of questionnaire, in-depth interview, and focus group discussion. The results show that the overall average of the factors affecting theeffectiveness of crime prevention and suppression was high. The average of the policetransformational leadership was the highest, followed by the organizational culture, thecross functional team, the strategy formulation, the evaluation, and last, the managementresources. Meanwhile, the overall average of the level of effectiveness of crime prevention and suppression was high. The average of the police station service was thehighest, followed by the police function development, the performance enhancement,the function management reinforcement, and last, the people and network participation.The results of the stepwise multiple regression analysis from the predicted equation ofthe level of effectiveness and the factors affecting the effectiveness show positiverelationship (0.427) at a significance level of 0.01. The results of the stepwise multipleregression analysis from the predicted equation illustrate that the police transformationalleadership (MPL), the strategy formulation (SM), and the cross functional team (CFT)could predict the level of effectiveness of crime prevention and suppression (CE) at 37%(R2= 0.375), and the constant value of the equation in the form of raw scores wasCE = 2.912 + 0.260 (MPL) + 0.104 (SM) + 7.205 (CFT). As can be seen from thisequation, the police transformational leadership was the priority factor that affects theeffectiveness of crime prevention and suppression.